THE HARMONY OF HISTORICAL TRUTH AND ARTISTIC FICTION - Olimjon Dadamirzayev (Modern American Journals, 2026)
This article discusses the creative activity of great actors who left a bright mark on the formation of Uzbek theater with their talent.
Keywords: A. Ismatov, R. Khamroyev, Charles-Antoine, Louis Lumière, Auguste Lumière, art, theater, performance, culture, national spirituality, national color, tradition, patriotism, national pride, troupe, theatrical performance, director, cinematograph.